The Relationship between Work Motivation and Job Efficiency of Supply Analysts at Higher Education Institutions in Mahasarakham Province - Utakarn, Chalermchai (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
This research aimed to 1) study the work motivation of supply analysts at higher education institutions in Mahasarakham Province, 2) study the job efficiency of supply analysts at higher education institutions in Mahasarakham Province, and 3) study the relationship between work motivation and job efficiency of supply analysts at higher education institutions in Mahasarakham Province. The sample group consisted of 92 supply analysts at higher education institutions in Mahasarakham Province. The data collected by questionnaire. The statistical techniques were means, standard deviation, and Pearson correlation coefficient. The results of the research showed that: 1) Supply analysts at higher education institutions in Mahasarakham Province showed a high degree of agreement toward overall work motivation. 2) Supply analysts at higher education institutions in Mahasarakham Province showed a high degree of agreement toward overall job efficiency. 3) Work motivation was positively correlated with overall performance at a high level (r=0.81). When considering each aspect in order of relationship from highest to lowest, as follows: In terms of work itself, there was a high correlation (r=0.83); in terms of achievement, there was a high correlation (r=0.76); in terms of recognition, there was a high correlation (r=0.75); in terms of advancement, there was a moderate correlation (r=0.63); and in terms of responsibility, there was a moderate correlation (r=0.62), respectively, with statistical significance at the .01 level.